Immune Enhancing Properties of Safflower Leaf (Carthamus tinctorius) on Chicken Lymphocytes and Macrophages - Sung-Hyen Lee; Hyun S. Lillehoj; Robert A. Heckert; Soo-Muk Cho; Wenbin Tuo; Erik P. Lillehoj; Hye-Kyung Chun; Hong-Ju Park (The Journal of Poultry Science, 2008)
Safflower (Carthamus tinctorius) has been used as a traditional medicinal plant to enhance natural immunity and treat cancers. However, limited information exists on the mechanisms responsible for its immune enhancing properties. In this study, the immunostimulatory effects of a methanol extract of safflower leaf were assessed by in vitro lymphocyte proliferation, tumor cell cytotoxicity, and nitric oxide production by cultured chicken macrophages. A crude methanol extract of safflower leaf stimulated spleen lymphocyte proliferation and nitric oxide production, and inhibited the viability of tumor cells significantly greater than medium controls. Sequential gel filtration chromatographic separation of the methanol extract on Sephadex G-25 and Sephacryl S-200 columns resulted in a partially purified preparation that retained the ability to induce lymphoproliferation, tumor killing, and NO production. These results demonstrate for the first time that safflower leaf contains immunostimulatory and anti-tumor component(s) that may be potentially useful as a dietary immunomodulator for poultry.